Evaluation of cryptococcal antigen testing using a novel chemiluminescence assay in two medical centers of China - Tang, Zhuo-Yun; Xu, Ping; Wang, Zhong-Hao; Wang, Ting-Ting; Zhou, Dan; Ao, Ke-Ping; Song, Hua-Feng; Yin, Xiao-Yun; Li, Dong-Dong (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveThis study aimed to assess the efficacy of innovative Chemiluminescence Immunoassay (CLIA) in testing Cryptococcal Antigen (CrAg) across two medical centers, employing the FDA-approved CrAg Lateral Flow Assay (LFA) by IMMY as a reference standard.MethodsThe study encompassed patients diagnosed with cryptococcosis at West China Hospital of Sichuan University (HX) between July 2022 and May 2023, and Suzhou Fifth People’s Hospital (SZ) from September 2020 to September 2023. All specimens underwent simultaneous detection using the LFA (IMMY, Norman, USA) and CLIA (Chuanglan, Suzhou, China).ResultsA total of 628 patients were enrolled, revealing a remarkable 99.20% concordance between LFA and CLIA (623/628, 99.20%). The LFA exhibited a sensitivity of 96.83% (244/252) and specificity of 98.35% (179/182). Among the 42 patients with unaltered CrAg titers, the changes of Signal-to-Cut-Off ratio (ΔS/CO) results exhibited a noteworthy discrepancy, with 71.43% (30/42) demonstrating a decreasing trend in ΔS/CO of at least 10%.ConclusionsThe CLIA method demonstrated commendable specificity and sensitivity, exhibiting a high level of agreement with the FDA-approved LFA method. Additionally, CLIA demonstrated superior utility for treatment monitoring compared to LFA, offering continuous insight into the fluctuation of CrAg concentrations.